The Use of Diamond for Energy Conversion System Applications: A Review - K. I. B. Eguiluz; J. M. Peralta-Hernández; A. Hernández-Ramírez; J. L. Guzmán-Mar; L. Hinojosa-Reyes; C. A. Martínez-Huitle; G. R. Salazar-Banda (International Journal of Electrochemistry)
Catalytic layers of polymer electrolyte membrane fuel cell (PEMFC) electrodes are usually composed of platinum nanoparticles dispersed on an electron conductive carbon support, which can undergo several degradation processes like dissolution of Pt and carbon corrosion under PEMFC working conditions. In this context, the major advantage of conductive boron-doped diamond (BDD) surfaces is their mechanical and chemical stability. BDD is also considered as a good substrate for studying the intrinsic properties of deposited catalysts, avoiding some problems encountered with other substrates, that is, surface corrosion, oxide formation, or electronic interactions with the deposit. Thus, the first part of this review summarized the surface modification of BDD materials, with emphasis in different techniques, to improve the catalytic efficiency of supported catalysts for PEMFCs. In addition, it is known that graphite carbon or lithium metal alloys used in advanced lithium-ion high-energy batteries suffer morphological changes during the charge-discharge cycling, which in turn results in a very poor cycle life. Thus, the use of diamond materials in these applications was also reviewed, since they have very stable surfaces and exhibits excellent electrochemical properties when compared with other carbon forms like glassy carbon and highly oriented pyrolytic graphite.